iFrost smart refrigerator / Nurul Syahirah Othman … [et al.] - Othman, Nurul Syahirah; Razman, Nur Aliah Farhana; Suffian, Ain Nurhasnifa; Mohd Sar, Farzana Afrina; Mohamad Roseli, Nur Hazwani (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Refrigerator is one of the valuable household appliances to keep foods and drinks cool by pushing a liquid refrigerant through a sealed system which causes it to vaporize and draw heat out of the fridge. Additionally, refrigerators are also useful home appliances that help the disabled people to store their medicines at cold temperature to avoid any exposure, however it also has its own challenges like smells, narrow spaces and does not have any advanced technology. iFrost Smart Refrigerator is a new refrigerator where consumers can gain the benefit from iFrost home application with the aim to enhance the advance of the technology that can help the households and disability people at the same time. iFrost smart refrigerator uses LCD display with IOS system, ice cream maker with any functions machines, also provides a built-in internal camera that connected with iFrost home application also has a sensor to neutralize and identify the foul gasses. Moreover, iFrost smart refrigerator also provides smart child lock to prevent any accidents since the iFrost smart refrigerator has focused to disabled people for instance the household with autistic children and cognitive disabilities. iFrost home application is a user-friendly application that helps consumers to control iFrost smart refrigerator remotely from their smartphone at home which can help the consumer to adjust the temperature of their iFrost smart refrigerator through the applications which as per the reported inconsistent temperature is one of the common problems (Morin, 2024). This iFrost smart refrigerator has a high potential in the market because of its integration with smart home ecosystems and also the market growth and adoption to 159 Melaka International Intellectual Exposition (MIIEX’2024) technology. The result of iFrost smart refrigerator in home appliances could be more beneficial among the seniors and disabled people because it can provide an increase of independent feeling, safety, and convenience of ease all around.